Sand-blasting treatment as a way to improve the adhesion strength of hydroxyapatite coating on titanium implant; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Grubova I. Yu. Irina Yurievna; Pryamushko T. S. Tatiana Sergeevna; Surmeneva M. A. Maria Alexandrovna; Korneva O. S. Olga Sergeevna; Epple M.; Prymak O.; Surmenev R. A. Roman Anatolievich (Modification of materials with particle beams and plasma flows, 2017)
Title screen